Vostok-2018: Another sign of strengthening Russia-China ties. Not an alliance, but defense cooperation is growing - Brian G. Carlson (Stiftung Wissenschaft und Politik (SWP), 2018)
Russia's recent Vostok-2018 military exercises, in which China's People's Liberation Army (PLA) participated for the first time, were another milestone in the increasingly close defense relationship between the two countries. Only a few years ago, Russia used these and other exercises to prepare its forces for the possibility of war with China. Now, at a time of strain in both countries' relations with the West, China's participation is a sign of the value that both sides attach to their relationship. The two countries are not about to form a military alliance, but their growing defense cooperation is likely to have a significant impact on global politics in the coming years.
Keywords: 320